THE ROLE OF SPEAKING SKILL IN DEVELOPING PROFESSIONAL COMPETENCE OF MEDICAL STUDENTS OF HIGHER EDUCATIONAL INSTITUTIONS IN THEIR LANGUAGE PROFICIENCY OF ENGLISH - Mamirbaeva Dina; Dastenova Firuza Andreyevna (PEDAGOGS, 2024)
Annotation: The article deals with importance of speaking skills in the English language for medical students of higher educational institutions. The article discusses problems encountered by students during learning English and several suggestions are given for teachers of English in order to help learners overcome these challenges. The article also describes new pedagogical technologies which can be used at the English classes of medical students for improving speaking skill.